COMMUNITY PERCEPTIONS AND USE OF REPRODUCTIVE HEALTH SERVICES IN RURAL INDIA - Nirmala. M. (JTH: Journal of Technology and Health, 2025)
This study aimed to explore the perceptions, barriers, and usage patterns of reproductive health services among women in rural areas of Uttar Pradesh and Bihar. A mixed-method cross-sectional study was conducted with 420 women aged 18–45. Quantitative data were collected through structured surveys, while qualitative insights were gathered via in-depth interviews and focus group discussions with local stakeholders. Descriptive statistics and logistic regression were used to analyze quantitative data, and thematic analysis was applied to qualitative data. While 84.3% of participants were aware of antenatal care, only 61.2% completed the recommended visits. Similarly, institutional delivery awareness was high (91.5%), yet only 67.8% utilized it. Key barriers included distance to health facilities, need for spousal permission, fear of mistreatment, and cultural taboos. Trust in ASHA workers was high, but confidence in the formal healthcare system remained low. The study reveals a clear mismatch between awareness and utilization of reproductive health services in rural India. Culturally sensitive, community-led strategies are necessary to enhance trust, reduce barriers, and improve equitable access to maternal and reproductive care.